War, Migration and the Origins of the Thai Sex Industry - Brodeur, Abel; Lekfuangfu, Warn N.; Zylberberg, Yanos (Université d'Ottawa | University of Ottawa, 2017)
This paper analyzes the determinants behind the spatial distribution of the sex industry in Thailand. We relate the development of the sex industry to an early temporary demand shock, i.e., U.S. military presence during the Vietnam War. Comparing the surroundings of Thai military bases used by the U.S. army to districts close to unused Thai bases, we find that there are currently 5 times more commercial sex workers in districts near former U.S. bases. The development of the sex industry is also explained by a high price elasticity of supply due to female migration from regions affected by an agricultural crisis. Finally, we study a consequence induced by the large numbers of sex workers in few red-light districts: the HIV outbreak in the early 1990s.
Keywords: persistence; industry location; sex industry; HIV/AIDS